2021
DOI: 10.1177/02692163211017383
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the COVID-19 pandemic for improving outpatient neuropalliative care: A qualitative study of patient and caregiver perspectives

Abstract: Background: COVID-19 has impacted persons with serious illness, including those with chronic, neurodegenerative conditions. While there are several reports on COVID-19’s impact on inpatient palliative care, literature is limited about the impact on outpatient care which may be more relevant for these patients. Aim: To generate a person-centered description of the impact of COVID-19 from the perspectives of patients living with neurodegenerative disease and caregivers to improve outpatient palliative care deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(93 citation statements)
references
References 38 publications
2
91
0
Order By: Relevance
“…According to the GRADE approach, only one study presented high quality (Rainero et al, 2021) and three a moderate quality (Lai et al, 2020;Giebel et al, 2020b;Macchi et al, 2021), whereas most of the included research showed very low-to-low quality. Cross-sectional study design, not validated scales, selfreport measures, and video or telephone interviews were the encountered limitations.…”
Section: Content Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the GRADE approach, only one study presented high quality (Rainero et al, 2021) and three a moderate quality (Lai et al, 2020;Giebel et al, 2020b;Macchi et al, 2021), whereas most of the included research showed very low-to-low quality. Cross-sectional study design, not validated scales, selfreport measures, and video or telephone interviews were the encountered limitations.…”
Section: Content Resultsmentioning
confidence: 99%
“…One of the few moderate quality studies according to the GRADE approach provided a person-centered description of the impact of the COVID-19 pandemic, whose results can be considered an exhaustive overview of the main themes that also emerged from other semi-structured interviews and open-ended surveys (Macchi et al, 2021). Besides the increased caregiver strain, disruption to the delivery of healthcare and supportive services was deeply perceived.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maintaining connections and providing psychological and social support to family members were challenging on virtual platforms. In another study, Macchi et al 14 describe the impact of COVID-19 from the perspective of caregivers and patients living with chronic neurodegenerative conditions who were enrolled in a US randomized trial of integrated, outpatient palliative care. 13 Disruption of ambulatory health care services, increasing social isolation and caregiver strain were not fully addressed by telecommunication.…”
mentioning
confidence: 99%